2019
DOI: 10.1101/794255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic contributions to hemisphere asymmetry in healthy brain, aging, and Parkinson’s disease

Abstract: Hemispheric asymmetry in neuronal processes is a fundamental feature of the human brain and drives symptom lateralization in Parkinson's disease (PD), but its molecular determinants are unknown. Here, we determine epigenetic differences involved in hemispheric asymmetry in the healthy and the PD brain. Neurons of the healthy brain exhibit numerous hemispheric differences in DNA methylation, which affect genes implicated in neurodegenerative diseases.In PD patients, hemispheric asymmetry in DNA methylation is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 99 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…This study also identified leukocyte genes whose methylation correlated with fecal butyrate levels in patients. To connect these butyrate-associated changes in peripheral methylation to changes within the brain, the researchers compared the identified leukocyte genes to previous work that identified genes with altered methylation in prefrontal cortical neurons (Li et al, 2020). They found significant overlap and correlated likelihood of methylation in Parkinson's disease patients for the leukocyte and neuronal genes, suggesting the potential for decreased butyrate levels to contribute to neurological changes through effects on brain DNA methylation (Xie et al, 2022).…”
Section: Gut-brain Axismentioning
confidence: 99%
“…This study also identified leukocyte genes whose methylation correlated with fecal butyrate levels in patients. To connect these butyrate-associated changes in peripheral methylation to changes within the brain, the researchers compared the identified leukocyte genes to previous work that identified genes with altered methylation in prefrontal cortical neurons (Li et al, 2020). They found significant overlap and correlated likelihood of methylation in Parkinson's disease patients for the leukocyte and neuronal genes, suggesting the potential for decreased butyrate levels to contribute to neurological changes through effects on brain DNA methylation (Xie et al, 2022).…”
Section: Gut-brain Axismentioning
confidence: 99%
“…Although epigenome-wide association studies (EWAS) have demonstrated altered DNAm patterns in individuals with PD in comparison to healthy subjects, the majority of findings were not replicable between studies (Masliah et al, 2013;Moore et al, 2014;Henderson-Smith et al, 2019;Li et al, 2020;Marshall et al, 2020;Vallerga et al, 2020;Henderson et al, 2021;Kia et al, 2021;Nabais et al, 2021;Kaut et al, 2022) (Supplementary Tables S1, S2). However, PD-related DNAm changes in particular genes, such as CYP2E1, have been reported in brain and blood across multiple studies (Kaut et al, 2012;Henderson-Smith et al, 2019;Kaut et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…Abnormal cerebral specialization in PD has been shown in studies from molecular biology and neuroimaging. For example, the asymmetry of DNA methylation in prefrontal cortex neurons is greater in PD patients than healthy controls, and has been linked to the disease course (Li et al, 2020). Diffusion tensor imaging studies also indicate abnormal structural asymmetry of the bilateral substantia nigra in PD patients (Prakash et al, 2012).…”
Section: Introductionmentioning
confidence: 99%